Centralized scheduling contention resolution for wireless metropolitan area networks - LU Wen-yan1; JIA Wei-jia1; WANG Guo-jun1; DU Wen-feng1 (Tongxin xuebao)
A novel centralized scheduling contention resolution （CSCR） was presented for the contention problem in PMP model of wireless metropolitan area networks. In each time frame, by estimating the number of active subscriber stations （SSs）, the base station （BS） provides an optimal window to all SSs. Each SS then individually participates with this win-dow in transmission. In comparison with the contention resolution based on truncated binary exponential backoff （BEB） algorithm given by IEEE 802.16, the CSCR resolution is not only easy to be implemented and more efficient in utilizing the transmission opportunities, but also can reduce the delay of admission. This was proved by our theoretical analysis and simulations.